2014
DOI: 10.1158/1535-7163.mct-13-0794
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Therapy Using Dovitinib and ICI182.780 (Fulvestrant) Blocks Tumoral Activity of Endometrial Cancer Cells

Abstract: Mutations in fibroblast growth factor receptor 2 (FGFR2) have been recently described as a molecularspecific feature in endometrial carcinomas and the presence of activated FGFR2 mutations is associated with poor prognosis. For that reason, inhibition of FGFR2 could be a therapeutic target in the treatment of endometriod carcinomas. In this work, we investigated the antitumoral activity of dovitinib (a multiple kinase inhibitor) in human endometrial cancer cell (ECC) lines. We found that dovitinib caused cell … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Although dovitinib shows wide ranges of IC50 in many types of cancer cells, this study demonstrated that relatively low concentrations of dovitinib could exert a stimulating effect on the BMP-2-induced osteoblast differentiation of C2C12 cells without significant cytotoxicity. As mentioned in previous reports, dovitinib showed anti-cancer activity through inhibition of FGFRs, PDGFRs, and VEGFRs ( Angevin et al, 2013 ; Eritja et al, 2014 ; Kim et al, 2011 ; Milowsky et al, 2014 ). However, in C2C12 cells, BMP-2 increased the proliferation of C2C12 cells and dovitinib did not exert significant cytotoxicity.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Although dovitinib shows wide ranges of IC50 in many types of cancer cells, this study demonstrated that relatively low concentrations of dovitinib could exert a stimulating effect on the BMP-2-induced osteoblast differentiation of C2C12 cells without significant cytotoxicity. As mentioned in previous reports, dovitinib showed anti-cancer activity through inhibition of FGFRs, PDGFRs, and VEGFRs ( Angevin et al, 2013 ; Eritja et al, 2014 ; Kim et al, 2011 ; Milowsky et al, 2014 ). However, in C2C12 cells, BMP-2 increased the proliferation of C2C12 cells and dovitinib did not exert significant cytotoxicity.…”
Section: Discussionsupporting
confidence: 52%
“…Dovitinib (TKI-258) was originally developed as a multi-targeted receptor tyrosine kinase (RTK) inhibitor and has a potent inhibitory effect on the activities of the Class III (FLT3/c-Kit), Class IV (FGFR1/3), and Class V (VEGFR1-4) RTKs ( Lopes de Menezes et al, 2005 ; Porta et al, 2015 ). In the previous reports, dovitinib has been used as an anti-cancer agent undergoing preclinical or clinical trials ( Angevin et al, 2013 ; Eritja et al, 2014 ; Kim et al, 2011 ; Milowsky et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was discovered that TKI258 enhances ER-a expression in FGFR2-mutant EC cells. Blocking one signal pathway is often not sufficient to cause tumor regression completely; thus, the combination of TKI258, which targets FGFR2, with a selective ER antagonist, fulvestrant, has resulted in a significantly higher inhibition of cell growth than TKI258 treatment alone [88]. Future studies with the combination of target therapies will be guided by strategies to decrease toxicity and increase response rates.…”
Section: Potential Development Issuesmentioning
confidence: 99%
“…-mutant cell lines up-regulated ERα and synergized with fulvestrant to inhibit proliferation(149). Additionally, over-expression of ERα was shown to rescue HHUA cells from MEK inhibition(86).…”
mentioning
confidence: 99%